Evaluating the efficiency of dual-use technology development programs from the R&D and socio-economic perspectives - Lu W.-M.; Kweh Q.L.; Nourani M.; Huang F.-W. (Elsevier Ltd, 2023)
This study applies a network data envelopment analysis model called network slacks-based measure (NSBM) to examine the R&D efficiency and socio-economic efficiency of Taiwan's dual-use (military and general public) technology development programs. We also employ the additive super-efficiency model to distinguish programs at different stages and conduct an analysis on the strengths and weaknesses of internal resource utilization. The results of this study show that the R&D efficiency is substantially higher than the socio-economic efficiency. Among the dual-use technology development programs, material and chemical engineering programs demonstrate relatively higher performance. This study provides insights into the policy of resource utilization. 2015 Elsevier Ltd.